Analisis Pengendalian Piutang di PT Kereta Api Indonesia (Persero) - Apriliani Sri Lestari; Neneng Weti Isnawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze receivables control at PT Kereta Api Indonesia (Persero) using the COSO (2013) framework, which includes five main components: Control Environment, Risk Assessment, Control Activities, Information and Communication, and Monitoring. The research method used is descriptive qualitative, with data collection techniques in the form of interviews, observations, and documentation. The object of this research is the Collection Section of PT Kereta Api Indonesia (Persero), which is responsible for managing the company's accounts receivable. The results showed that in the Control Environment, the company has demonstrated a commitment to integrity through anti-bribery policies, AKHLAK culture, and the application of technology-based systems. Risk Assessment is carried out by utilizing the SMARTKA application to monitor risks in real-time, supported by inherent risk analysis and periodic evaluations, so that potential losses due to bad debts can be minimized. In Control Activities, the company uses technology such as virtual accounts and is developing new applications to improve efficiency and mitigate risks, such as the risk of fraud and bad debts. In Information and Communication, the company ensures relevant information is collected through SOPs, the use of SAP applications, and effective internal and external communication through correspondence, mediation, and digital platforms such as WhatsApp. The Monitoring component is implemented through periodic evaluations involving internal audits by SPI, preparation of Audit Results Reports (LHA), and coordination meetings with management to follow up on findings. In conclusion, the five components of internal control according to COSO (2013) have been implemented and function well at PT Kereta Api Indonesia (Persero).